What are the environmental factors that affect respiratory viral pathogen transmission and outcomes? A scoping review of the published literature - Spencer, Elizabeth; Brassey, Jon; Pluddemann, Annette (Frontiers in Environmental Health, 2024)
Introduction Respiratory viral pathogens are a major cause of morbidity and mortality, and there is a need to understand how to prevent their transmission. Methods We performed a scoping review to assess the amount and scope of published research literature on environmental factors, including meteorological factors and pollution, that affect the transmission of respiratory viral pathogens. We used Joanna Briggs Institute methodology for conducting a scoping review. We searched the electronic databases: MEDLINE, Register of Controlled Trials (Cochrane CENTRAL), TRIP database, WHO Covid-19 Database, Global Index Medicus, LitCovid, medRxiv, and Google Scholar. We included studies on environmental exposures and transmission of respiratory viruses (including but not restricted to: influenza, respiratory syncytial virus (RSV), human coronaviruses, viral pneumonia). Results The searches identified 880 studies for screening; after screening we included 481 studies, including 395 primary studies and 86 reviews. Data were extracted by one reviewer (ES) and independently checked by a second reviewer for accuracy (AP). All primary studies were observational, mostly using an ecological design; 2/395 primary studies were prospective cohorts. Among the primary studies, 241/395 were on SARS-CoV-2/COVID-19; 95 focussed on influenza; the remaining 59 reported on RSV, other coronaviruses, and other respiratory viruses. Exposures were most commonly temperature (306 primary studies) and humidity (201 primary studies); other commonly reported exposures were air pollution, wind speed, precipitation, season, and UV radiation. It was frequently reported, but not consistently, that temperature, humidity and air pollution were positively correlated with COVID-19 cases/deaths; for influenza, season/seasonality was commonly reported to be associated with cases/deaths. Discussion The majority of studies reported on SARS-CoV-2/COVID-19 and were of ecological design. Few prospective cohort studies have been done for any respiratory virus and environmental exposures. Understanding the role of environmental factors on transmission is limited by the lack of prospective cohort studies to inform decision making. Systematic Review Registration https://osf.io/ntdjx/, identifier: 10.17605/OSF.IO/NTDJX.